Plant-derived natural products and combination therapy in liver cancer - Wang, Yuqin; Li, Jinyao; Xia, Lijie (Frontiers in Oncology, 2023)
Liver cancer is one of the malignant cancers globally and seriously endangers human health because of its high morbidity and mortality. Plant-derived natural products have been evaluated as potential anticancer drugs due to low side effects and high antitumor efficacy. However, plant-derived natural products also have defects of poor solubility and low bioavailability. In recent years, a growing numbers of plant derived natural products have been used in combination therapy of liver cancer with conventional chemotherapeutic agents, which has improved clinical efficacy through multiple mechanisms, including inhibition of tumor growth, induction of apoptosis, suppression of angiogenesis, enhancement of immunity, reversal of multidrug resistance and reduction of side effects. The therapeutic effects and mechanisms of plant-derived natural products and combination therapy on liver cancer are reviewed to provide references for developing anti-liver-cancer strategies with high efficacy and low side effects.